EXPLORING THE RELATIONSHIP BETWEEN GRAMMARLY PERCEPTIONS AND EFL UNDERGRADUATE STUDENTS’ ACADEMIC WRITING ACHIEVEMENT - febrika; Bambang Eko Siagiyanto; Dedy Subandowo (English Education Study Program, 2026)
In the context of academic writing, English as a Foreign Language (EFL) undergraduate students seem to utilize AI-based grammar checkers, such as Grammarly, to assist them in their writing. This current study aimed to investigate the correlation between EFL undergraduate students' perceptions towards the use of Grammarly and their writing achievements in academic writing. Additionally, the study sought to determine the extent to which these perceptions affect their writing achievements in academic writing. This research employed a correlational research design which collecting the data through a questionnaire and writing test from 62 students of English Education Study Program at Universitas Muhammadiyah Metro. The findings showed that more than half participants, 51.61%, held a